Fiscal Policy Guidelines: Between Bidenomics and Debt Brake - ZG Überblick (Wirtschaftsdienst)
Abstract The upcoming federal elections open a new window of opportunity for financial policy in Germany. Representatives of different parties are advocating a new direction for fiscal policy. US President Biden has already set a new course in the US, for example in the areas of climate policy and tax competition. These are likely to have a direct impact on policy in Europe. This raises the exciting question of what lessons German economic policy can learn from the economic and financial policy realignment in the US.